A new atherosclerotic lesion probe based on hydrophobically modified chitosan nanoparticles functionalized by the atherosclerotic plaque targeted peptides - Park, Yeongsoon; Hong, Hai-Yan; Moon, Hyun Jeong; Lee, Byung-Heon; Kim, In-San; Kwon, Ick Chan; Rhee, Iyehan (ELSEVIER SCIENCE BV, 2008)
We developed a new imaging probe for atherosclerotic lesion imaging by chemically conjugating an atherosclerotic plaque-homing peptide (termed the AP peptide) to hydrophobically modified glycol chitosan (HGC) nanoparticles. The AP peptide was previously discovered by using an in vivo phage display screening method. HGC nanoparticles were labeled with the near-infrared (NIR) fluorophore Cy5.5, yielding nanoparticles 314 nm in diameter. The binding characteristics of nanoparticles to cytokine (TNF-alpha)-activated bovine aortic endothelial cells (BAECs) were studied in vitro under static conditions and in a dynamic flow environment. AP-tagged HGC-Cy5.5 nanoparticles (100 mu g/ml, 2 h incubation) bound more avidly to TNF-alpha-activated BAECs than to unactivated BAECs. Nanoparticles were mostly located in the membranes of BAECs, although some were taken up by the cells and were visible in the cytoplasm, suggesting that the AP peptides in HGC nanoparticles retained target selectivity for activated BAECs. Binding selectivity of AP-tagged HGC-Cy5.5 nanoparticles was also studied in vivo. NIR fluorescence imaging demonstrated that AP-tagged HGC-Cy5.5 nanoparticles bound better to atherosclerotic lesions in a low-density lipoprotein receptor-deficient (Ldlr(-/-)) atherosclerotic mouse than to such lesions in a normal mouse. These results suggest that the newly designed AP-tagged HGC-Cy5.5 nanoparticles may be useful for atherosclerotic lesion imaging, and may also be employed to elucidate pathophysiological changes, at the molecular level, on atherosclerotic endothelium. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: SELF-ASSEMBLED NANOPARTICLES; BEARING 5-BETA-CHOLANIC ACID; E-SELECTIN; IN-VIVO; MAGNETIC-RESONANCE; PHAGE DISPLAY; ADHESION; INFLAMMATION; DELIVERY; CELLS